Constructing Functional Ionic Membrane Surface by Electrochemically Mediated Atom Transfer Radical Polymerization. (29th September 2016) - Ran, Fen; Li, Dan; Wu, Jiayu
Abstract : The sodium polyacrylate (PAANa) contained polyethersulfone membrane that was fabricated by preparation of PES-NH2 via nonsolvent phase separation method, the introduction of bromine groups as active sites by grafting α -Bromoisobutyryl bromide, and surface-initiated electrochemically atom transfer radical polymerization (SI-eATRP) of sodium acrylate (AANa) on the surface of PES membrane. The polymerization could be controlled by reaction condition, such as monomer concentration, electric potential, polymerization time, and modifier concentration. The membrane surface was uniform when the monomer concentration was 0.9 mol/L, the electric potential was −0.12 V, the polymerization time was 8 h, and the modifier concentration was 2 wt.%. The membrane showed excellent hydrophilicity and blood compatibility. The water contact angle decreased from 84° to 68° and activated partial thromboplastin increased from 51 s to 84 s after modification of the membranes.